AB0369 Adult-onset still's disease treatment predictors at 1-year follow-up in a single rheumatologic centre experience. (12th June 2018) - Giannotta, M.; Cacciapaglia, F.; Giannini, M.; Nivuori, M.; Fanizzi, R.; Lopalco, G.; Laselva, G.; Scioscia, C.; Iannone, F.
Abstract : Background: Adult-onset Still's disease (AOSD) is a rare systemic inflammatory disorder mainly characterised by persistent high spiking fevers, evanescent rash, and joint involvement. Data on the efficacy of biologic therapy in the management of AOSD 1 is increasing and represents a breakthrough in the management of patients with AOSD refractory to corticosteroids (CS) or conventional (c) DMARDs. Objectives: We aimed to evaluate possible predictor on the need to use a biologic agent in the management of AOSD patients. Methods: In this retrospective monocentric study we evaluated AOSD patients followed in our outpatient's clinic since 2010 with at least 1 year follow-up. Clinical manifestations, joint involvement, CS and c- or bDMARD use were main outcome measures. T-test or ANOVA and Chi-squared were used to compare continuous or categorial data, when appropriate, and the odds ratio (OR) for which condition had an influence on clinical outcome was calculated. Results: We evaluated 28 AOSD patients (mean age 43±14 years; median disease duration 3 (95%CI 2.5–17.3) months). All patients at baseline were treated with a median CS of 18.7 (95%CI 14.3–24.8) mg/die prednisone equivalent dose, and median methotrexate (MTX) dose of 15 (95%CI 13.4–16.28) mg/week. After 1 year follow-up, in the 8 patients (28.6%) that needed to start a bDMARD (4 anti-IL1; 3 anti-IL6 and 1 anti-TNF), we observed that baseline joint involvement was the more prevalent manifestation of the disease with higher DAS28 compared to those patients still on CS +MTX (DAS28 3.8±1.2 vs 2.8±1.1, respectively p=0.03). Moreover, we showed that clinical manifestations of systemic involvement (i.e. fever, rash, organomegaly and anaemia) were associated with a protective risk to start a bDMARD at 1 year (OR 0.4 95% CI 0.2–0.76). Consistently, in those patients with concomitant elevated ESR (>20 mm/h), CRP (>15 mg/L) and ferritin (>250 ng/ml) levels at baseline, we observed a low risk to start a bDMARD at 1 year follow-up (OR 0.4 95% CI 0.18–0.87). Conclusions: In our cohort about one third of AOSD patients required to be treated with a bDMARD at 1 year follow-up, mainly if joint involvement was the predominant clinical manifestation at disease onset. Systemic manifestations of the disease seem to benefit from high dose CS+MTX combination therapy. Further studies with more extensive cases are necessary. Reference: [1] Cavalli G, Franchini S, Aiello P, Guglielmi B, Berti A, Campochiaro C, Sabbadini MG, Baldissera E, Dagna L. Efficacy and safety of biological agents in adult-onset Still's disease. Scand J Rheumatol2015;44(4):309–14. Disclosure of Interest: None declared